Konsep Koperasi Dalam Tinjauan Filsafat Hukum Ekonomi - mahmudah, Nur (Fakultas Syariah IAIN Kediri, 2022)
Welfare is one of the goals of the societies that make up the state. There are various ways to fulfill it, one of which is a cooperative. A cooperative is an association of people or entities that gives people the freedom to enter and leave as members, to work together in a family manner in running a business to fulfill or improve the welfare of its members. Mohammad Hatta as the originator of Article 33 of the 1945 Constitution has formulated his philosophical thoughts about the economic system of the Indonesian nation, he emphasized that the principle of kinship is cooperatives, this law is a working effort towards the national economy. Based on these provisions, cooperatives are a constitutionally valid system. At a macro level, cooperatives are envisioned as the backbone of the Indonesian economy based on the principle of kinship to create prosperity and community welfare. In its application, many cooperatives have succeeded, but also many have failed, some have stumbled over fraud cases and so on. Based on this, the question raised in this paper is, how is the ideology, concept and legal structure of cooperatives based on law in Indonesia in terms oEf the philosophy of economic law? To analyze it, the author uses the library research method by collecting valid and relevant data and then comparing, criticizing and analyzing, to draw the right conclusions. The theory of approach is the school of utulitarianism which argues that the purpose of law is the greatest welfare for the people, and legal evaluation is carried out based on the consequences resulting from the process of applying the law. Adherents of this school consider that the purpose of law is to provide as much benefit and happiness as possible to citizens. The purpose of law according to Jeremy Bentham is to realize the greatest happiness of the greatest number, aka the purpose of legislation is to produce happiness for society. Then what about the cooperative system as a system of national economic realization, whether this system by law has fulfilled the principles of utilitarianism. The result of this research is that happiness, defined as the general welfare, must be above all individual happiness in the eyes of the constitution. The argument is that the happiness of all people involved in an event or endeavor is not the happiness of one person alone, but includes all the happiness of its members in general. The happiness of one person should not be considered more important than the happiness of another, hence like the King and subordinates should be treated equally. Thus an action or endeavor is considered good when happiness outweighs unhappiness, and the happiness of everyone involved should be treated in the same way.